Triagem de isolados clínicos de Leishmania sp. para sequenciamento genômico - Takahashi, Talita Yuri (2020)
Leishmaniasis is a group of infectious tropical disease caused by protozoan from genus Leishmania and transmitted to humans through bites of infected sand flies. Visceral Leishmaniasis (VL) is the most severe clinical form of the disease and can be lethal if untreated or treatments fail. Brazil composes one of the 13 countries with the highest number of new VL cases in the world caused by Leishmania infantum, with a great focus on Northeastern. Treatments are poorly developed and the fatality rate expands every year affecting mainly children under 10 years-old. Recent study has shown the occurrence of a similar Crithidia fasciculata parasite in clinical isolates (LVH60 and LVH60a) in a fatal VL case. The disease onset is related to parasite/host interface factors. Parasite identification and genomic analyses of the pathogen enable to understand the intrinsic factors and genetic diversity of parasite related to the disease outcome and response to treatment. Thus, one of the aims in this study was to perform the screening of clinical isolates from patients diagnosed with VL in Aracaju - Sergipe region, to select samples for Whole-Genome Sequencing (WGS) in Illumina platform for obtaining complete genomic sequences of parasites capable of causing VL in this endemic area. The screening encompassed the parasite morphological analysis, molecular characterization of conserved genomic regions through DNA sequencing analysis and molecular phylogenetics. Engendered data were useful for constructing an informative panel about the analyzed samples, which guided to the selection of clinical isolates for genome sequencing. In parallel, this study also had as aim to systematize the genome analyzes of WGS data obtained from previous work, which will assist the Comparative Genomic analyses between Leishmania and Crithidia-like to our group’s further studies. Finally, a polished genome of Crithidia-like parasite was obtained from a clonal sample of LVH60a with Oxford Nanopore Technology (ONT), which resulted in a final genome assembly of 38 contigs and a predicted genome size of 34.4 Mb in length. This study was essential to understand the occurrence of non-Leishmania parasites in the endemic region of LV in Aracaju and for studying the genome and genetic variation to lead future strategy analyses and intervention in public health caused by this new parasite.